Implementation of Complete Systemic Land Registration Program's Policy (PTSL) in Mojomanis Village, Kwadungan District, Ngawi Regency (Universitas PGRI Madiun, 2021)
This study aims to determine the implementation of the Complete Systematic Land Registration (PTSL) program policy in Mojomanis Village, Kwadungan District, Ngawi Regency. 24 of 1997 which was later replaced by Regulation of the Minister of Agrarian Affairs and Spatial Planning / Head of the National Land Agency of the Republic of Indonesia No. 12 of 2017 concerning Land Registration. The type of research carried out is empirical or sociological, namely research that examines the law in reality or reality in the community/regarding its behavior to find out the implementation and implementation constraints of the Complete Systematic Land Registration (PTSL) program in Mojomanis Village, Kwadungan District, Ngawi Regency according to the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency No. 6 of 2018 concerning Complete Land Registration in accordance with Village Minister Regulation Number 14 of 2020. The results of this study explain that the implementation of Complete Systematic Land Registration in Mojomanis Village, Kwadungan District, Ngawi Regency has been running well and in accordance with established regulations. The inhibiting factors in the implementation of Complete Systematic Land Registration in Mojomanis Village, Kwadungan District, Ngawi Regency are divided into two, namely technical and legal obstacles. One of the efforts to overcome these obstacles is by using the method of deliberation and sitting together